Advances of Mechanisms-Related Metabolomics in Parkinson’s Disease - Zhang, Yanyan; Li, Jie; Zhang, Xiao; Song, Dongdong; Tian, Tian (Frontiers in Neuroscience, 2021)
Parkinson’s disease (PD) is a multifactorial disorder characterized by progressively debilitating dopaminergic neurodegeneration in the substantia nigra and the striatum, along with various metabolic dysregulations and molecular abnormalities. Metabolomics is an emerging study and has been demonstrated to play important roles in describing the complex human diseases by integrating endogenous and exogenous sources of alterations. Recently, an increasing number of researches have shown that the metabolomics profiling hold great promise to provide unique insights into the molecular pathogenesis and be helpful of identifing candidate biomarkers for clinical detection and therapies of PD. In this review, we briefly summarize recent findings and analyse the application of molecular metabolomics in familial and sporadic PD from different domains, including genetic mutations, mitochondrial dysfunction and dysbacteriosis, with a brief overview of diagnostic biomarkers to represent the functional stage and improve therapeutic strategies to postpone or hinder the disease progression.